A strategy of innovation through the development of a portfolio of innovation capabilities. Issue 1 (4th February 2014) - Holtzman, Yair
Abstract : Purpose: – The purpose of this paper is to introduce the value in developing a portfolio of capabilities to fuel innovation. The author's experience suggests that a disciplined focus developing a portfolio of innovation capabilities is critical in the global competitive landscape. Traditionally, the business world has always been focussed on developing sustainable competitive advantage. This is optimal, but we find more and more situations where this notion of building a sustainable competitive advantage is no longer possible. In 2013 it is rare for a company to maintain a truly lasting advantage. Many times, the very success of the initiative drives competition, which in turn weakens the advantage. Innovation as a portfolio of capabilities that can continuously morph based on the traditional forces of the market can prove much more powerful. This paper discusses what is needed in developing a strategy for developing a portfolio of capabilities and the challenges that companies face in undertaking this goal. Design/methodology/approach: – General viewpoint based upon over 20 years of consulting work experience by an expert in the field of innovation, new product development, and research and development. Findings: – The relevance and importance of a novel approach to thinking about innovation is very creative and valuable to companies that are constantly struggling with the development of new products. Practical implications: – This is a novel approach to thinking about developing new products, capabilities, or services within an organization. Originality/value: – The paper is extremely valuable in that it highlights a new way to think about developing innovation and new product capabilities, new product features, in a competitive global environment.